Designing effective public engagement: the case study of Future Melbourne 2026. Issue 2 (3rd April 2019) - Katsonis, Maria
Abstract: Public engagement can enrich policy-making, bringing a diversity of views and voices to policy decisions being made. By placing the experience of those affected by the outcome at the center of deliberations, it can also lead to better informed policies and programs aligned with citizens' needs. The engagement process strengthens transparency and accountability in addition to building civic capacity. This paper examines the role of public engagement through the lens of a community engagement project for a 10-year local government plan which set outs the future direction of city life. The case offers insights for effective public engagement including the need for strong leadership from decision makers, whether elected officials or senior public servants, and a commitment to inclusion, participation, and transparency in decision-making.